2021
DOI: 10.1038/s41598-021-87044-x
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature (< 200 °C) degradation of electronic nicotine delivery system liquids generates toxic aldehydes

Abstract: Electronic cigarette usage has spiked in popularity over recent years. The enhanced prevalence has consequently resulted in new health concerns associated with the use of these devices. Degradation of the liquids used in vaping have been identified as a concern due to the presence of toxic compounds such as aldehydes in the aerosols. Typically, such thermochemical conversions are reported to occur between 300 and 400 °C. Herein, the low-temperature thermal degradation of propylene glycol and glycerol constitue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 33 publications
0
37
0
Order By: Relevance
“…The data in Figure 3 are consistent with low concentrations being used in early EC products, but could also indicate that there was degradation or evaporation during aging. Hydroxyacetone, which was present in all products, was likely a degradation product of the solvents [ 48 , 49 , 50 ]. Although flavor chemical concentrations are low, some of these chemicals may be harmful.…”
Section: Discussionmentioning
confidence: 99%
“…The data in Figure 3 are consistent with low concentrations being used in early EC products, but could also indicate that there was degradation or evaporation during aging. Hydroxyacetone, which was present in all products, was likely a degradation product of the solvents [ 48 , 49 , 50 ]. Although flavor chemical concentrations are low, some of these chemicals may be harmful.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a study by Jaegers et al [44] found that pyrolysis alone in an anaerobic environment was not able to induce thermal degradation of PG and VG at low temperatures (< 200˚C), despite previous studies observing degradation at temperatures as low as 149˚C during vaping [45]. However, when heated in an aerobic environment, thermal decomposition was observed at 133 and 175˚C, both without and with the addition of metal oxides Cr 2 O 3 and ZrO 2 [44], suggesting that oxidation is a key process during vaping. In combination with the results shown here, evidence highly suggests that pure pyrolysis alone may not be the only pathway for VEA degradation.…”
Section: Plos Onementioning
confidence: 97%
“…tested, including S. gordonii ( 20 , 22 ). Oxidation and decomposition upon heating of the universal carrier components, glycerol and propylene glycol ( 4 ), can result in the formation of formaldehyde and acetaldehyde ( 29 ). It has been reported that these chemicals are bactericidal and have a negative effect on the oral microbiota ( 30 ).…”
Section: Resultsmentioning
confidence: 99%